2011
DOI: 10.4168/aair.2011.3.2.138
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Association Between Leukocyte Adhesion Deficiency Type I and Psoriasis in Humans

Abstract: The β2 integrins are expressed exclusively on leukocytes and participate in many immune and inflammatory processes. This subfamily comprises four heterodimeric glycoproteins with a common β-subunit, designated β2 (CD18). Spontaneous mutations of the CD18 gene result in leukocyte adhesion deficiency type I (LAD-I). Low level of CD18 expression has also been implicated in the pathogenesis of psoriasis. We here describe a child with recurrent skin infections without pus formation, persistent gingivitis and period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This deficiency manifests in recurrent skin infections without pus formation, persistent gingivitis, periodontitis, and psoriasis. This patient showed persistent neutrophilia, reduced CD18 expression on CD4 ϩ T cells (which normally express ␣ L ␤ 2 and ␣ M ␤ 2 but not ␣ X ␤ 2 ), and normal expression of CD18 and CD11c on PMN (70). These observations suggest the importance of ␣ M ␤ 2 but not of ␣ X ␤ 2 in the resolution of inflammation and for the inhibition of autoimmune diseases such as psoriasis associated with defective M egress.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This deficiency manifests in recurrent skin infections without pus formation, persistent gingivitis, periodontitis, and psoriasis. This patient showed persistent neutrophilia, reduced CD18 expression on CD4 ϩ T cells (which normally express ␣ L ␤ 2 and ␣ M ␤ 2 but not ␣ X ␤ 2 ), and normal expression of CD18 and CD11c on PMN (70). These observations suggest the importance of ␣ M ␤ 2 but not of ␣ X ␤ 2 in the resolution of inflammation and for the inhibition of autoimmune diseases such as psoriasis associated with defective M egress.…”
Section: Discussionmentioning
confidence: 69%
“…Particularly, low levels of CD18 (␤ 2 ) expression on leukocytes have been implicated in the pathogenesis of psoriasis and different granulomas (69). A patient with a rare variant of LAD-1 with defective CD11b expression, but normal CD18 expression, was described recently (70). This deficiency manifests in recurrent skin infections without pus formation, persistent gingivitis, periodontitis, and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, unlike human psoriasis, IMQ-induced murine dermatitis does not progress to a chronic stage. According to our data presented in this study and previous reports, reduced CD18 expression levels are found on blood leukocytes in psoriasis patients (35)(36)(37)(38)(39), and in a recent independent study, an inflammatory CLA + Vg9Vd2 T cell subset in human blood capable of infiltrating the skin has been identified in psoriasis patients (25). To enhance these in part rather correlative data, we provide direct evidence for a causal relationship between reduced CD18 expression levels on immune cells and expansion of inflammatory skin-tropic gd T cells potentiating psoriasiform dermatitis in the chronic CD18 hypo PL/J psoriasis mouse model that closely mimics human psoriasis.…”
Section: Discussionmentioning
confidence: 80%
“…+ ab and gdTCR low gd T cells with a memory phenotype predominate in the skin infiltrate in CD18 hypo PL/J psoriasiform dermatitis Because normally, CD18 is highly expressed on ab and gd T cells and expression of CD18, ICAM-1, or ICAM-2 is altered in certain psoriasis patients (35)(36)(37)(38)(39), we set out to analyze the impact of reduced CD18 levels on gd T cell function and inflammatory cytokine and marker expression in psoriasiform dermatitis using the CD18 hypo PL/J mouse model. To characterize the skin infiltrate of affected CD18…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation